2009
DOI: 10.1139/h09-004
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels of older community-dwelling adults are influenced by summer weather variables

Abstract: Adequate daily physical activity (PA) is important for maintaining functional capacity and independence in older adults. However, most older adults in Canada do not engage in enough PA to sustain fitness and functional independence. Environmental influences, such as warmer daytime temperatures, may influence PA participation; however, few studies have examined the effect of summertime temperatures on PA levels in older adults. This investigation measured the influence of summertime weather variables on PA in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
2
34
1
1
Order By: Relevance
“…Many studies have used self-report accounts of physical activity that are subject to recall biases [27]. Objective measures of physical activity, including accelerometry, provide more accurate measurements but are subject to variability due to different factors including weather and season [28]. Our results demonstrated that ambulatory physical activity can be reliably measured using an accelerometer despite such influences.…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have used self-report accounts of physical activity that are subject to recall biases [27]. Objective measures of physical activity, including accelerometry, provide more accurate measurements but are subject to variability due to different factors including weather and season [28]. Our results demonstrated that ambulatory physical activity can be reliably measured using an accelerometer despite such influences.…”
Section: Discussionmentioning
confidence: 69%
“…Current literature demonstrates a small but statistically significant effect of weather variables on daily PA in various populations including COPD (5), community dwelling elderly (6-7-8-9), healthy adults (10-11-12), and functionally impaired elderly (13). However, within these studies, there is wide variation in the definition of daily PA (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 41 Japanese community dwelling healthy elderly, step count increased within an ambient temperature range of -2°C to 17°C and decreased over a range of 17°C to 29°C (8). In community dwelling elderly in Canada, daily PA peaked at 20°C and decreased with temperatures above 30°C (6). Although these studies indicate a potential effect of weather on daily PA levels, there is no agreement regarding the thresholds for temperature and temperature change that result in changes in daily PA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,24-26 However, studies using accelerometers to capture PA have found a decline in PA with extreme heat, 11,26 specifically, a decline in PA at temperatures >30 C among older adults in Canada and a decline in PA over a range from 17 C to 29 C among older adults in Japan. 11,26 We collected data over two fall/winter seasons and one spring/summer season in a region of Ontario, Canada, where outdoor maximum temperature ranged from À6.5 C to 27.6 C; temperatures were likely not high enough to demonstrate a decrease in PA during hot days. Nevertheless, both healthy adults and adults with knee OA appear to be more active when outdoor temperatures are moderate.…”
Section: Discussionmentioning
confidence: 99%